Small irrigation users' perceptions of environmental change, impacts, and response in Nepal. (9th August 2021) - Parajuli, Jagadish; Eakin, Hallie; Chhetri, Netra
ABSTRACT: This paper focuses on smallholders' perceptions of environmental variability and its impacts, their responses, and the role of Water Users' Associations (WUA) in governing the irrigation system in response to observed environmental changes. Our research recognizes that farmers' adaptations emerge from placed-based experience, yet adaptation policy and programmes may not recognize the heterogeneity of place-based experience. Fifteen farmer-managed irrigation systems from five districts of Nepal were selected as research sites, representing different ecological regions. Data were collected from household surveys and key informant interviews; the quantitative data were analysed using descriptive statistics. Our study reveals that the perception of environmental change differs across the ecological gradients and irrigators' physical position along the irrigation canals. Labour scarcity, investment in technology, access to non-farm income, information on environmental variability, and sociodemographic factors also influence irrigators' perceptions. Irrigators responded by adjusting irrigation amounts, improving irrigation infrastructure and altering irrigation rules, and using local knowledge and technology. WUA assist irrigators by mobilizing labour for canal maintenance, managing water distribution, monitoring irrigation systems, and collecting service fees. Our finding supports policy initiatives that recognize the importance of WUA, the differential and situated experience of climate risk, and the need for place-specific adaptation options for Nepalese farmers.